Poor long-term recovery after critical COVID-19 during 12 months longitudinal follow-up. (February 2023) - Larsson, Ing-Marie; Hultström, Michael; Lipcsey, Miklos; Frithiof, Robert; Rubertsson, Sten; Wallin, Ewa
Abstract: Objectives: This study aimed to describe the burden of illness and impact on health and working situation among former intensive care patients treated for COVID-19. Methods: A prospective cohort study was performed at one intensive care unit of a university hospital in Sweden during the first wave of COVID-19 in spring 2020. The burden of illness in health status, cognitive, physical, and psychological outcomes, and working situation were assessed at four and 12 months after discharge from intensive care, using nine validated instruments. Results: Forty-six participants treated for COVID-19 participated in both follow-ups and were included in this study. General fatigue was reported by 37 of 46 participants (82%) at both follow-ups (p = 1.000). For overall health status 28 (61%) participants at the first follow-up and 26 (57%) (p = 0.414) at the second reported lower values than the general population. Cognitive impairment was seen in 22 (52%) participants at four months and in 13 (31%) at 12 months (p = 0.029). The proportion of participants on sick-leave decreased between the first and second follow-up (24% vs 13%, p = 0.025), but the proportion of participants working full-time was almost the same at both follow-ups (35% vs 37%, p = 0.317). Conclusions: The burden of illness of patients treated in intensive care due to COVID-19 included cognitive, physical, and psychological impacts. Cognitive functions were improved after 12 months, but no clear improvements could be distinguished in the physical or psychological outcome. Higher burden of illness was associated with inability to return to work.